Safety and immunogenicity of novel recombinant BCG and modified vaccinia virus Ankara vaccines in neonate rhesus macaques. - Rosario, M; Fulkerson, J; Soneji, S; Parker, J; Im, E; Borthwick, N; Bridgeman, A; Bourne, C; Joseph, J; Sadoff, J; Hanke, T (2010)
Although major inroads into making antiretroviral therapy available in resource-poor countries have been made, there is an urgent need for an effective vaccine administered shortly after birth, which would protect infants from acquiring human immunodeficiency virus type 1 (HIV-1) through breast-feeding. Bacillus Calmette-Guérin (BCG) is given to most infants at birth, and its recombinant form could be used to prime HIV-1-specific responses for a later boost by heterologous vectors delivering the same HIV-1-derived immunogen. Here, two groups of neonate Indian rhesus macaques were immunized with either novel candidate vaccine BCG.HIVA(401) or its parental strain AERAS-401, followed by two doses of recombinant modified vaccinia virus Ankara MVA.HIVA. The HIVA immunogen is derived from African clade A HIV-1. All vaccines were safe, giving local reactions consistent with the expected response at the injection site. No systemic adverse events or gross abnormality was seen at necropsy. Both AERAS-401 and BCG.HIVA(401) induced high frequencies of BCG-specific IFN-gamma-secreting lymphocytes that declined over 23 weeks, but the latter failed to induce detectable HIV-1-specific IFN-gamma responses. MVA.HIVA elicited HIV-1-specific IFN-gamma responses in all eight animals, but, except for one animal, these responses were weak. The HIV-1-specific responses induced in infants were lower compared to historic data generated by the two HIVA vaccines in adult animals but similar to other recombinant poxviruses tested in this model. This is the first time these vaccines were tested in newborn monkeys. These results inform further infant vaccine development and provide comparative data for two human infant vaccine trials of MVA.HIVA.